Effect of diabetes duration and glycaemic control on 14-year cause-specific mortality in Mexican adults: a blood-based prospective cohort study - Herrington, W; Alegre-Díaz, J; Wade, R; Gnatiuc, L; Ramirez, R; Hill, M; Solano, M; Baigent, C; Lewington, S; Collins, R; Tapia-Conyer, R; Peto, R; et al. (Elsevier, 2018)
Background Diabetes is a cause of at least one-third of all Mexican deaths at ages 35-74, with the excess mortality due mainly to vascular disease, renal disease, infection, and acute diabetic crises. Methods 100,000 women and 50,000 men aged ≥35 years from Mexico City were recruited into a blood-based prospective study between 1998-2004 and followed for cause-specific mortality. Cox models assessed associations between diabetes duration (<5, ≥5 to <10, ≥10 years) and HbA1c (<9% versus ≥9%) with risk of mortality from vascular disease, renal disease, and infection, among those with diabetes. Findings Of 133,662 participants aged 35-74 with complete data and no other chronic disease, 16,940 had previously-diagnosed diabetes and 6541 had undiagnosed diabetes. Among those with previously-diagnosed diabetes, glycaemic control was poor (median HbA1c 8.9% [interquartile range 7.0-10.9%) and was even worse among those with longer diabetes duration. Compared to those without diabetes, the death rate ratios (RRs) at ages 35-74 for the combination of vascular, renal or infective causes increased from 3·0 among those with undiagnosed diabetes to 4·5 for those with diabetes duration <5 years, 6·6 for those with duration ≥5 to <10 years and 11·7 for those with duration ≥10 years (all p<0·00001). At a given diabetes duration, RRs were nearly twice as big for those with HbA1c ≥9% (median 10·9%) as those with HbA1c <9% (median 7·0%). Diabetes was not strongly associated with the combination of deaths from other causes excluding acute glycaemic crises. Mortality among those without diabetes was not strongly associated with HbA1c. Interpretation In Mexico, the rates of death from causes strongly associated with diabetes increased steeply with duration of diabetes and were higher still among those with poor glycaemic control. Delaying the onset of diabetes, as well as improving its treatment, is essential to reduce premature adult mortality.